Evaluation of mechanical cervical dislocation, captive bolt, carbon dioxide, and electrical methods for individual on-farm euthanasia of broiler breeders - R.S. Boyal; R.J. Buhr; C.E. Harris; L. Jacobs; D.V. Bourassa (Poultry Science, 2022)
ABSTRACT: Efficacious euthanasia by applying manual cervical dislocation can be difficult on large and mature poultry. The challenge with using manual cervical dislocation is that the strength required to hold heavy poultry and swiftly apply cervical dislocation can be physically impossible for most people. Therefore, alternative methods of euthanasia are needed for mature and large poultry. Mechanical cervical dislocation using the Koechner Euthanizing Device (KED), captive bolt using the Turkey Euthanasia Device (TED), carbon dioxide (CO2), and electrical euthanasia were evaluated for use on 65-wk-old broiler breeders at flock termination. Following application of each method, physiological reflexes including the eye nictitating membrane reflex, mouth gaping, and body movement, broken skin, blood loss, kill success, time to cessation of heartbeat, and blood plasma corticosterone levels were assessed. Birds euthanized using the KED had longer response durations for eye nictitating membrane (91 s) and reflexive mouth gaping (161 s) compared to TED, CO2, and electrical euthanasia (0–7 s). Body movement durations were also longer for KED (214 s) and TED (209 s) than for CO2 and electrical euthanasia (0–8 s). The highest percentages of broken skin (93%) and blood loss (96%) were observed for TED, followed by KED (71%, 68%), then CO2 (0%, 6%) and electrical euthanasia (0%, 3%). No significant differences (P = 0.1781) were observed for kill success rates with 98% for KED, 100% for TED, 97% for CO2, and 100% for electrical euthanasia at 4-min. Time to heartbeat cessation did not differ between KED (659 s), TED (427 s), or CO2 (583 s) euthanasia methods. No heartbeat was detected following electrical euthanasia. Blood plasma corticosterone levels did not differ between preeuthanasia or posteuthanasia from any of the methods applied. Based on these results each euthanasia method is acceptable for use with broiler breeders.